Effects of probiotics on atopic dermatitis: a randomised controlled trial. Issue 9 (29th April 2005) - Weston, S; Halbert, A; Richmond, P; Prescott, S L
Abstract : Background: The aim of the study was to investigate the effects of probiotics on moderate or severe atopic dermatitis (AD) in young children. Methods: Fifty six children aged 6–18 months with moderate or severe AD were recruited into a randomised double blind placebo controlled trial in Perth, Western Australia; 53 children completed the study. The children were given a probiotic (1×10 9 Lactobacillus fermentum VRI-033 PCC; Probiomics) or an equivalent volume of placebo, twice daily for 8 weeks. A final assessment at 16 weeks was performed. Results: The main outcome measures were severity and extent of AD at the end of the study, as measured by the Severity Scoring of Atopic Dermatitis (SCORAD) index. The reduction in the SCORAD index over time was significant in the probiotic group (p = 0.03) but not the placebo group. Significantly more children receiving probiotics (n = 24, 92%) had a SCORAD index that was better than baseline at week 16 compared with the placebo group (n = 17, 63%) (p = 0.01). At the completion of the study more children in the probiotic group had mild AD (n = 14, 54%) compared to the placebo group (n = 8, 30%). Conclusion: Supplementation with probiotic L fermentum VRI-003 PCC is beneficial in improving the extent and severity of AD in young children with moderate or severe disease.